Respuesta :

Answer:

[tex]y=\frac{4}{5}e^{t}-\frac{4}{5}e^{-\frac{2}{5}t}[/tex]

Step-by-step explanation:

The given equation 5y'' + 3y' - 2y =0 can be written as

[tex](5D^{2}+3D-2)y(t)=0[/tex]

Solving for complementary function we have Roots of [tex](5D^{2}+3D-2)[/tex] as follows

[tex](5D^{2}+5D-2D-2)[/tex]

[tex]5D(D+1)-2(D+1)=0\\\\(5D-2)(D+1)=0\\\\\therefore D=-1\\D=+2/5[/tex]

Thus the complementary function becomes

y=[tex]y=c_{1}e^{m_{1}t}+c_{2}e^{m_{2}t}[/tex]

where

[tex]m_{1},m_{2}[/tex] are calculated roots

thus solution becomes

[tex]y=c_{1}e^{-t}+c_{2}e^{\frac{2}{5}t}[/tex]

Now to solve for the coefficients we use the given boundary conditions

[tex]y(0)=0\\\\\therefore c_{1}+c_{2}=0\\\\y'(0)=-c_{1}+\frac{2}{5}c_{2}=2.8\\\\\therefore c_{2}+\frac{2}{5}c_{2}=2.8\\\\c_{2}=2\\\\\therefore c_{1}=-2}[/tex]

hence the solution becomes

[tex]y=-2e^-{t}+2e^{\frac{2}{5}t}[/tex]

ACCESS MORE